Efficacy and safety of bispecific antibodies therapy for relapsed or refractory multiple myeloma: a systematic review and meta-analysis of prospective clinical trials - Wang, Xin; Zhao, Ailin; Zhu, Jinbing; Niu, Ting (Frontiers in Immunology, 2024)
Bispecific antibody (BsAbs) therapy represents a promising immunotherapeutic approach with manageable toxicity and noteworthy preliminary efficacy in treating patients with relapsed or refractory multiple myeloma (RRMM). The objective of this systematic review and meta-analysis was to compare the efficacy and safety of B-cell maturation antigen (BCMA)-targeted BsAbs and non-BCMA-targeted BsAbs in the treatment of RRMM patients.PubMed/MEDLINE, Web of Science, EMBASE, Cochrane Library and meeting libraries were searched from inception to August 16th, 2023. The efficacy evaluation included the complete objective response rate (ORR), complete response (CR) rate, stringent CR (sCR) rate, partial response (PR) rate, and very good PR (VGPR) rate. The efficacy evaluation included any grade adverse events (AEs) and grade ≥ 3 AEs.Fourteen studies with a total of 1473 RRMM patients were included. The pooled ORR of the entire cohort was 61%. The non-BCMA-targeted BsAbs group displayed a higher ORR than the BCMA-targeted BsAbs group (74% vs. 54%, P < 0.01). In terms of hematological AEs, BCMA-targeted BsAbs therapy exhibited higher risks of neutropenia (any grade: 48% vs. 18%, P < 0.01; grade ≥ 3: 43% vs. 15%, P < 0.01) and lymphopenia (any grade: 37% vs. 8%, P < 0.01; grade ≥ 3: 31% vs. 8%, P = 0.07). Regarding non-hematological AEs, there were no significant differences in the risks of cytokine release syndrome (CRS, any grade: 64% vs. 66%, P = 0.84; grade ≥ 3: 1% vs. 1%, P = 0.36) and infections (any grade: 47% vs. 49%, P = 0.86; grade ≥ 3: 24% vs. 20%, P = 0.06) between the two groups. However, non-BCMA-targeted BsAbs therapy was associated with a higher risk of immune effector cell-associated neurotoxicity syndrome (ICANS, any grade: 11% vs. 2%, P < 0.01) and lower risks of fatigue (any grade: 14% vs. 30%, P < 0.01) and pyrexia (any grade: 14% vs. 29%, P < 0.01).This analysis suggest that non-BCMA-targeted BsAbs therapy may offer a more favorable treatment response and tolerability, while BCMA-targeted BsAbs therapy may be associated with diminished neurotoxic effects.